Disclosing Our Relationships to Disabilities: An Invitation for Disability Studies Scholars - OToole, Corbett (Disability Studies Quarterly, 2013)
In this paper, I address the question of public nondisclosure of one’s relationship to disability within Disability Studies. I argue that we need to examine our reluctance to support public disclosure, open academic inquiries into public signifiers, encourage public disclosure, and use signifiers of one’s relationship to disability in all Disability Studies contexts. I tease out the importance of public disclosure while maintaining personal privacy related to impairment information. I explore the embedded ableism in nondisclosure. And I challenge Disability Studies to address nondisclosure as a significant barrier in the field. Specific recommendations for disclosure surrounding our relationship to disability are provided